PENGARUH ENTREPRENEURIAL MARKETING TERHADAP KINERJA UMKM DENGAN PENGGUNAAN PEMASARAN MEDIA SOSIAL SEBAGAI MEDIASI - Wulandari, Suci; Jannah, Miftahul; Afifah, Zainiyatul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of entrepreneurial marketing on the performance of MSMEs with the use of social media marketing as a mediating variable. The research method employed is a quantitative approach. The data used consist of both primary and secondary sources. The sample in this study comprises 100 respondents, selected using probability sampling with a simple random sampling technique. The respondent characteristics include MSMEs that have been established for more than one year, MSMEs engaged in trade, manufacturing, and services, and MSMEs actively using social media located in Bangkalan Regency. Data collection was carried out through observation, interviews, and questionnaire distribution, and the data were processed using SmartPLS version 4. The results of the study indicate that entrepreneurial marketing influences MSME performance through social media marketing as a mediating variable. Furthermore, the path coefficient analysis shows that social media marketing plays a significant mediating role in the relationship between entrepreneurial marketing and MSME performance.